(untitled) (Yangi O’zbekistonda Tabiiy va Ijtimoiy-gumanitar fanlar respublika ilmiy amaliy konferensiyasi, 2025)
The study of the topic of the development of communicative abilities is pertinent today due to changes in current education. Three areas where socioeconomic changes are affecting education include unrestricted personal growth, creative initiative, and student autonomy.